Association of early loss of primary functional patency of arteriovenous access with mortality in incident hemodialysis patients: A nationwide population-based observational study. Issue 31 (August 2018) - Wu, Chung-Kuan; Lin, Chia-Hsun; Hsu, Chih-Cheng; Tarng, Der-Cherng; Kor, Chew-Teng; Chen, Yi-Chun; Wu, Chia-Lin; Chang, Chia-Chu
Abstract : Abstract: The long-term survival and life quality of hemodialysis (HD) patients depend on adequacy of dialysis via a well-functioning vascular access. Loss of primary functional patency (PFP) of an arteriovenous access (AVA) eventually happens in HD patients. The association between time to loss of PFP of AVAs and mortality in HD patients remains unclear. The retrospective nationwide population-based cohort study compared the hazards of mortality with time to loss of PFP. We enrolled 1618 adult incident HD patients who received HD via AVAs for at least 90 days between January 1, 2001 and December 31, 2013. They were divided into early (⩽1 year) and late (>1 year) loss of PFP according to intervention-free intervals (time from first successful cannulation to percutaneous transluminal angioplasty [PTA]). Patients with early loss of PFP were older; had more clinic visits annually and higher Charlson comorbidity index scores; were associated with higher proportions of diabetes mellitus, coronary artery disease, heart failure, stroke, chronic obstructive pulmonary disease, cancer, and use of arteriovenous graft, diuretic, antidiabetic drugs, and aspirin (all P < .05). Kaplan–Meier analysis revealed the cumulative incidence of mortality was significantly higher in patients with early loss of PFP (log-rank test; P < .01). After adjustment, early loss of PFP was independently associated with a higher risk of mortality (adjusted hazard ratio, 1.21; 95% confidence interval, 1.01−1.45; P = .045). Regarding the impact of time to PTA on mortality, patients with intervention-free intervals of ⩽3, 3 to 6, and 6 to 12 months had similar trends of lower survival. Early loss of PFP is an independent risk factor for mortality in chronic HD patients. A comprehensive strategy for maintaining PFP and reducing dysfunctional AVAs may be required. Abstract : Supplemental Digital Content is available in the text